RECHARGE WELLS MODEL BASED ON SHAPE FACTORS FOR FLOOD MANAGEMENT IN KLOJEN DISTRICT, MALANG CITY - Rokhmawati, Azizah; Fachrurozi Ilhamsyah; Bambang Suprapto (Journal Innovation of Civil Engineering (JICE), 2023)
Urban flood areas hit various regions in Indonesia, such as what happened in Malang City. Flooding occurred in several areas of Klojen District, including Wilis Street, LetJen Suprapto Street in Samaan Village, Bareng Raya Street II in Bareng Village, Retawu Street, and Pulosari Street. This research uses a recharge well model based on shape factors to discuss flood mitigation. Data analysis includes existing floods, conditions of the study area, and an applied model adjusted to soil permeability in the research area. They were mapping the area (A) and coefficient C using ArcGIS 10.8 2023 software. The model applied is an infiltration well design constructed from a concrete buis at the top and soil pores at the bottom. The design rainfall calculation results are 592.112 mm/day. The results of the analysis show that there are a total of 30 channels from Samaan Village, Bareng Village, and Gading Kasri Village, whose channel capacity is unable, causing flooding. The geometric factor value of 3.14 m has a planned water inflow discharge of 1.7626 m3/second. Klojen sub-district requires 66 recharge wells to overcome the flooding. The application for constructing infiltration wells was carried out only in the Gading Kasri sub-district area, namely 11 infiltration wells. The infiltration well is planned to use a concrete buis with dimensions of 50x100 m, height L as deep as 2 m, bottom of porus in 1 m, and total depth of channel H is 3 m. Keywords: Recharge Wells; Shape Factors; Flood Management; Klojen Sub District.